Pulse Breath Water - Prpa, Mirjana; Tatar, Kivanc; Pasquier, Philippe; Riecke, Bernhard E. (MUTEK International Festival of Digital Creativity and Electronic Music: MUTEK_IMG + VR Salon, 2016)
pulse_breath_water is an immersive virtual environment that depends on and reacts to the human interaction/reaction to these three substantial elements: pulse, breath, and water. The pulse of a participant’s breath provokes and challenges an interaction between a user and a system, and this reflects in changes in water behaviour in the scene. The system “senses” the participant, while the participant’s The system “senses” the participant, while the participant’s breathing feeds the system. The process is a symbiotic play between internal human processes [biosensing the participant’s breath] and the system’s agency that guides the participant between the state of calm and the state of anxiety.
Keywords: Riecke; Riecke_2016; bernhard-riecke; biofeedback-in-VR; biofeedbackInVR; kivanc-tatar; mirjana-prpa; philippe-pasquier; pulse-breath-water; talkWithoutPaper